The Effect Of Non-Physical Work Environment And Workload On Job Satisfaction Mediated By Reward At Pt Module Intracs Yasatama Cikarang - Sri Wahyuningsih; Fitri Rezeki; Retno Purwani Setyaningrum (UNIVED Press, 2024)
This study aims to determine The Effect of Non-Physical Work Environment and Workload on Job Satisfaction Mediated by Reward at PT Module Intracs Yasatama Cikarang. Respondents of this study were 90 respondents and this study used a quantitative approach with the SmartPLS 3.0 data processing application. The results of this study found that 1. Non-Physical Work Environment has no effect on Job Satisfaction, 2. Workload has no effect on Job Satisfaction, 3. Reward affects Job Satisfaction, 4. Non-Physical Work Environment has no effect on Reward, 5. Workload affects Reward, 6. Reward as a mediating variable has a role in strengthening the effect of Non-Physical Work Environment on Job Satisfaction although it cannot be said to have a significant effect, 7. Reward as a mediating variable has a role in strengthening the effect of Workload on Job Satisfaction.